2008
DOI: 10.1080/07315724.2008.10719701
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a PDA-based Dietary Assessment and Intervention Program: A Randomized Controlled Trial

Abstract: DietMatePro does not appear to produce more valid data than paper-based approaches. DietMatePro may improve adherence to dietary regimens compared to paper-based methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 23 publications
(23 reference statements)
2
79
0
2
Order By: Relevance
“…For example, Beasley et al [26] reported a higher adherence to recommended energy, fat, saturated fat, and cholesterol intake in overweight-obese clients in the intervention group using feedback based on self-monitoring with an electronic food diary compared with the control group. However for the other interventions, dietitians identified patient characteristics such as the stage of change readiness as barriers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Beasley et al [26] reported a higher adherence to recommended energy, fat, saturated fat, and cholesterol intake in overweight-obese clients in the intervention group using feedback based on self-monitoring with an electronic food diary compared with the control group. However for the other interventions, dietitians identified patient characteristics such as the stage of change readiness as barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Other interventions sought to increase fibre intake, 44,45,55,59,[80][81][82] Comparators used in included studies Table 4 shows a summary of comparators used in the studies. Fourteen studies 44,[48][49][50][51]53,54,56,59,69,74,77,79,80 trialled the intervention against a non-intervention control group.…”
Section: Target Outcomes Of Included Studiesmentioning
confidence: 99%
“…The majority of interventions sought to reduce fat intake 44,45,[49][50][51]54,55,[58][59][60][61][62]64,65,[67][68][69][72][73][74][76][77][78][79][80][81][82][83] (28 interventions) and/or to increase fruit and vegetable intake 43,44,[47][48][49][50][51]55,56,58,59,62,67,68,[71][72][73]75,[80][81][82] (21 interventions). Other interventions sought to increase fibre intake, 44,45,55,59,…”
Section: Target Outcomes Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…El objetivo es evaluar los comportamientos del paciente en entornos naturales (la casa, el trabajo, el colegio, etc.). Existen estudios que demuestran que el uso de dispositivos móviles para completar los autoregistros mejora la adherencia al tratamiento (Beasley, Riley, A. Davis, & Singh, 2008) y los niveles de aceptación del mismo comparado con los autoregistros en lápiz y papel (Fowles & Gentry, 2008). …”
unclassified